인공적 도덕행위자(AMA)의 온톨로지 구축 - 박균열(Gyun-Yeol Park) (디지털콘텐츠학회논문지, 2019)
본 연구는 인공지능이 도덕적 행위자로서의 지위를 갖추기 위해 필요한 온톨로지를 구축하기 위한 기본 방향을 제시하는 데 목적을 둔다. 인공지능 기술이 날로 발전함에 따라서 인공지능의 도덕적, 법적 사안에 대한 논의가 심각하게 제기되고 있다. 법적 문제의 경우 규정 형태로 명시되어 있기 때문에 요목화하는 데 큰 어려움이 없지만 도덕적 사안에 대해서는 많은 난제가 기다리고 있다. 인공지능 자체에 도덕적 기능을 부여할 것인지, 만약 한다면 어느 수준으로 할 것인지, 인공지능을 도덕적 주체로 인정할 경우 사용자와 개발자, 그리고 관련 정책입안자들은 어떤 태도를 지향해야 하는지 등에 대한 논의를 해야 한다. 그중에서 이 연구는 인공지능 자체에 도덕적 기능을 부여할 수 있다고 가정하고, 어떻게 그 기능을 부여할 것인지에 대한 기본적인 골격을 제시하고자 한다. 이를 위해 본 연구는 인공지능의 윤리적 의사결정 메커니즘 모델과 관련한 이론을 고찰하고, 이를 위한 기본 알고리즘을 제안한다. 또한 이 연구는 이것이 갖는 윤리적 시사점을 제기함으로써 향후 보다 복합적이고 설명 가능한 인공적 도덕행위자의 온톨로지 정립에 기초자료를 제공할 수 있다. This study aims to provide a basic direction for the ontology of artificial intelligence which is needed to attain its status as a moral agent. With the ever-evolving artificial intelligence technology, discussions on the moral and legal issues of artificial intelligence are being seriously raised. As for legal matters, it is stated in the form of codes, so there are no major difficulties in making segmentations, but many challenges lie ahead on the moral issues. If the artificial intelligence itself is given moral functions, if at what level it will do, and if it is recognized as a moral subject, users, developers and relevant policymakers should discuss what attitude to pursue. The study, among other issues, assumes that the artificial intelligence itself can be given a moral function, and tries to present a basic framework for how to give it the moral function. For that purpose, this study reviewed the theories related to the ethical decision-making mechanism model of the artificial intelligence, and proposed a basic algorithm for the model. This study can also provide a basis for the establishment of a more complicated and explainable artificial moral agent's ontology in the future by bringing up its ethical implications. KCI Citation Count: 5